SHARIA-COMPLIANT MICROFINANCE AND LOCAL ECONOMIC DEVELOPMENT: THE ROLE OF BPRS UNDER ACEH’S SHARIA FINANCIAL INSTITUTION LAW (QANUN LKS) - Safprina Humaira (GREET, 2025)
This study investigates the role of Sharia-compliant rural banks (BPRS) in fostering inclusive and sustainable economic development in Aceh, Indonesia, under the Sharia Financial Institution Law (Qanun LKS). Employing a mixed-methods design that combines semi-structured interviews with 20 stakeholders, surveys of 100 clients, and regulatory analysis, the research addresses the gap in empirical studies on BPRS within a region governed entirely by Sharia-based financial regulations. Findings indicate that BPRS significantly expand financial inclusion, with 75% of surveyed clients reporting income growth after receiving financing and regions with active BPRS experiencing a 20% decline in poverty rates over five years. The institutions not only provide capital but also strengthen entrepreneurship, job creation, and local resilience, while their profit-sharing model fosters trust and inclusivity, particularly benefiting women entrepreneurs, evidenced by a 30% increase in female-owned businesses. Beyond financial services, BPRS contribute to community empowerment through training and social initiatives, aligning their mission with the maqasid al-shariah and Sustainable Development Goals (SDGs). However, challenges remain in regulatory compliance, governance structures, human resource capacity, and limited digital infrastructure, which restrict outreach and operational efficiency. This study argues that while BPRS have proven transformative in promoting poverty alleviation, gender equity, and inclusive growth, their long-term sustainability depends on strengthening institutional capacity, integrating digital technologies, and forging stronger partnerships with government and community organizations. The case of Aceh illustrates the potential of Sharia-compliant microfinance to serve as a model for ethical and context-sensitive financial development strategies across Indonesia and beyond.